APPLYING DRILLING TECHNIQUE TO ENHANCE STUDENTS’ PRONUNCIATION OF SUFFIX –ED IN REGULAR VERBS - Cici Fauzia; Muhammad Ihsan; Afifah (Datokarama English Education Journal, 2022)
This research aims to find out whether drilling technique can enhance students’ pronunciation of suffix –ed in regular verbs or not. The researcher applied true experimental design which involved the experimental class and control class. The population of this research was the eighth-grade students of MTsN 2 Palu; VIII A as the experimental class and VIII B as the control class. The researcher used a cluster random sampling technique. The instruments used to collect the data were tests, recordings, and observation sheets. The pre-test was conducted to measure the students’ pre-ability before obtaining the treatment and the post-test was to measure the students’ ability after obtaining the treatment. The data obtained from the scores of the students’ test were analyzed statistically. The result of data analysis shows that the alternative hypothesis of this research was accepted by regarding to the analysis of tcounted (2.84) was higher than ttable (1.69) by applying 0.05 level of significance with degree of freedom (df) is N1 + N2 – 2 = 29 which means that drilling technique can enhance students’ pronunciation of suffix –ed in regular verbs.